PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 7E TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Zomi Widya Putri (Departemen Matematika, 2019)
The mathematical communication ability is one of the goals of mathematics learning that must be achieved. However, the 7th grade of mathematics in Junior High School 2 Bukittinggi, students mathematical communication ability was not optimal yet. There are some effort that could be used to improve students mathematical communication ability. One of them by applying the 7E Learning Cycle model. The aims of this study was to describe whether the mathematical communication ability of students learning by using the 7E Learning Cycle model better than the students who learn using the direct one. This research used the quasy experiment types with the design of Static Group Design. The results show that the mathematical communication ability of students who learn using the 7E Learning Cycle model has increase. Furthermore, based on the result of the hypothesis test, it is find that the mathematical communication ability of students learning to use the 7E Learning Cycle model are better than the mathematical communication ability of students who learn using the direct learning model. So, it can be conclude that the 7E Learning Cycle model has an influence on students mathematical communication ability.Keywords – 7E LearningiCycle Model, Direct Learning Model, Mathematical Communication Ability.